2008
DOI: 10.3166/ga.21.53-66
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Coarse Bedload Transport Measured with Bedload Traps and Helley-Smith Samplers

Abstract: Gravel bedload transport rates were measured at eight study sites in coarse-bedded Rocky Mountain streams using 4-6 bedload traps deployed across the stream width and a 76 by 76 mm opening Helley Smith sampler. Transport rates obtained from bedload traps increased steeply with flow which resulted in steep and well-defined transport rating curves with exponents of 8 to 16. Gravel transport rates measured by the HelleySmith sampler started with much higher transport rates during low flows and increased less stee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
81
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 70 publications
(86 citation statements)
references
References 53 publications
5
81
0
Order By: Relevance
“…At the Brenno, the minimum threshold dimensionless shear stress θ c50,Min for the initiation of bedload motion has been calibrated to a value of 0.1 (Table 2). This corresponds to the findings of Lamb et al (2008) and Bunte et al (2013), who showed that in mountain rivers θ c may well assume values in this order of magnitude.…”
Section: Simulations For the Calibration Periodsupporting
confidence: 90%
See 2 more Smart Citations
“…At the Brenno, the minimum threshold dimensionless shear stress θ c50,Min for the initiation of bedload motion has been calibrated to a value of 0.1 (Table 2). This corresponds to the findings of Lamb et al (2008) and Bunte et al (2013), who showed that in mountain rivers θ c may well assume values in this order of magnitude.…”
Section: Simulations For the Calibration Periodsupporting
confidence: 90%
“…This is partly due to the complex measurement conditions in gravel-bed rivers (Bunte et al, 2008;Gray et al, 2010). Because of these difficulties, there are relatively few data sets available for deriving conceptual models or for validating and testing numeric models.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Measured m values are usually much larger than those derived from models. For example, Bunte et al (2008) reported m values ranging from about 7.5 to 16, using data obtained during the snowmelt period of American streams with portable bedload traps. Analysing bedload data sampled with Helley-Smith pressure difference samplers from a large number of streams, Barry et al (2004) found values of m in the range of about 1.5-4.0.…”
Section: Channel Bed Slopementioning
confidence: 99%
“…Many measurements have utilised box or tray samplers, and this approach is still common today. Hubbell (1964), Engel and Lam Lau (1981), Ergenzinger and de Jong (2003), Bunte et al (2008) and Holmes (2010), along with many others, have considered this technique. Some of the major shortcomings of this direct sampling method are the need for operators in the field, the limited range of conditions when measurements are possible, dangerous conditions during large floods, the impact on the flow introduced by the presence of the sampler, the lack of spatial/temporal resolution, the variable efficiency of samplers, the problems in obtaining continuous records and other difficulties specific to the particular samplers.…”
Section: Introductionmentioning
confidence: 99%